(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article deals with the problem of the dynamics of the Ukrainian folk proverbs about the Muscovites tradition. It is emphasized on folkloric transformation of semantic markers on popular evaluations of the socio-psychological type of a Moscovite. In the new socio-political conditions of Ukraine, the traditional image not only indicates the depth and versatility of people’s judgments about Ukraine / Russia relations, but also gaining new meanings. The modern values of the token "Moskal" are the result of the deep reflection of Ukrainians on the political, social and moral and ethical factors of the development of the nation. This traditionally negatively marked folk image is now gaining new meanings: 1) a soldier of a foreign army, who invaded the territory of Ukraine; 2) an immoral representative of Ukrainian society, a bearer of a destructive way of thinking, which, while living in Ukraine, hurts it from inside. Ukrainian social and household proverbs reflect the broad amplitude of popular assessments of this socio-psychological type and meaningful transformations dictated by the needs of the present.